Maternal prenatal immunity, neonatal trained immunity, and early airway microbiota shape childhood asthma development. Issue 12 (25th July 2022) - DeVries, Avery; McCauley, Kathryn; Fadrosh, Douglas; Fujimura, Kei E.; Stern, Debra A.; Lynch, Susan V.; Vercelli, Donata
Abstract: Background: The path to childhood asthma is thought to initiate in utero and be further promoted by postnatal exposures. However, the underlying mechanisms remain underexplored. We hypothesized that prenatal maternal immune dysfunction associated with increased childhood asthma risk (revealed by low IFN‐γ:IL‐13 secretion during the third trimester of pregnancy) alters neonatal immune training through epigenetic mechanisms and promotes early‐life airway colonization by asthmagenic microbiota. Methods: We examined epigenetic, immunologic, and microbial features potentially related to maternal prenatal immunity (IFN‐γ:IL‐13 ratio) and childhood asthma in a birth cohort of mother–child dyads sampled pre‐, peri‐, and postnatally ( N  = 155). Epigenome‐wide DNA methylation and cytokine production were assessed in cord blood mononuclear cells (CBMC) by array profiling and ELISA, respectively. Nasopharyngeal microbiome composition was characterized at age 2–36 months by 16S rRNA sequencing. Results: Maternal prenatal immune status related to methylome profiles in neonates born to non‐asthmatic mothers. A module of differentially methylated CpG sites enriched for microbe‐responsive elements was associated with childhood asthma. In vitro responsiveness to microbial products was impaired in CBMCs from neonates born to mothers with the lowest IFN‐γ:IL‐13 ratio, suggesting defective neonatal innate immunity in those who developed asthma during childhood. These infants exhibited a distinct pattern of upper airway microbiota development characterized by early‐life colonization by Haemophilus that transitioned to a Moraxella ‐dominated microbiota by age 36 months. Conclusions: Maternal prenatal immune status shapes asthma development in her child by altering the epigenome and trained innate immunity at birth, and is associated with pathologic upper airway microbial colonization in early life. Abstract : Through an integrated, inter‐generational approach, we characterized maternal and early‐life epigenetic, immunologic and microbial features that influence asthma development during childhood. We demonstrate that, in children of non‐asthmatic mothers, maternal prenatal immune status (IFN‐γ:IL‐13) shapes the child's path to asthma by altering the epigenome and trained innate immunity in the neonate, and promoting pathologic upper airway microbial colonization in early life. These results provide a novel framework for mechanistic research linking maternal prenatal health to childhood asthma pathogenesis. Abbreviations: CBMC, cord blood mononuclear cells; IFN, interferon; IL,  interleukin; LPS, lipopolysaccharide; PBMC, peripheral blood mononuclear cells; rRNA, ribosomal RNA